Arbuscular mycorrhizal fungi and Trichoderma longibrachiatum alter the transcriptome of Vicia villosa in response to infection by the fungal pathogen Stemphylium vesicarium - Ding, Tingting; Feng, Wei; Bai, Meiting; Gu, Lijun; Duan, Tingyu (BMC microbiology, 2025)
Leaf spot caused by Stemphylium vesicarium is a severe disease of Vicia villosa and first reported in 2019. Arbuscular mycorrhizal fungi (AMF) and Trichoderma are common beneficial microorganisms in soil that enhance plant resistance to pathogens. This study established a greenhouse experiment to examine the physiological and transcriptomic changes of V. villosa that were co-inoculated with the AMF Sieverdingia tortuosa and Trichoderma longibrachiatum to determine their effects on the development of resistance to disease. Infection by the pathogen reduced the shoot biomass of V. villosa. Individual inoculation or co-inoculation with AMF and T. longibrachiatum reduced the severity of disease and promoted defense-related reactions, such as the production of salicylic acid (SA), activity of phenylalanine ammonia lyase and chitinase. Inoculation of Trichoderma alone or in combination with AMF significantly increased the content of SA of the diseased V. villosa by 12.23% and 12.80%, respectively. Treatment with AMF alone significantly increased the chitinase activity of susceptible V. villosa by 6.4% compared with V. villosa only infected with S. vesicarium. Gene ontology terms that related to plant disease resistance, such as upregulated "Defense response", "Peroxidase activity", and "Signal acceptor activity", were significantly enriched in diseased plants that had been inoculated with S. tortuosa and T. longibrachiatum. However, they were not significantly enriched in susceptible plants that had not been inoculated with S. tortuosa and T. longibrachiatum. The expression of the genes that were involved in the Kyoto Encyclopedia of Genes and Genomes pathways "Isoflavonoid biosynthesis" and "Flavone and flavonol biosynthesis" and were related to disease defense was upregulated. Both of T. longibrachiatum and AMF exhibit significant potential in managing leaf spot disease caused by S. vesicarium in V. villosa. The mechanism includes the increased SA content as well as the expression of pathogen defense-related genes in plant. T. longibrachiatum alone and combined with AMF resulted in a significant increase in SA levels. Furthermore, AMF also significantly up-regulated the expression of NPR1-related genes, which are integral to systemic acquired resistance. Our findings underscore the efficacy of T. longibrachiatum and AMF as potential biological control agents, providing a promising strategy for the management of leaf spot disease in V. villosa.